A dual‐band circularly polarized planar monopole antenna for Wireless Local Area Network/Worldwide Interoperability for Microwave Access applications. Issue 2 (1st November 2018) - Yang, Dong; Zhai, Huiqing; Xue, Kun; Xi, Lei; Wu, Xinhua; Li, Yinhu
Abstract: In this letter, a new dual‐band circularly polarized (CP) planar monopole antenna is proposed. Simply by embedding an asymmetrical T‐shaped strip into the arc‐shaped feedline, dual‐band operation and CP radiation can be obtained. Furthermore, adding an inverted‐L‐shaped strip to the previous designing, the axial ratio bandwidths (ARBWs) can be greatly improved. After fabricating and then testing, the measured results indicate that the impedance bandwidths (IBWs) below 10‐dB can reach 240 MHz (2.39‐2.63 GHz) and 2.73 GHz (3.85‐6.58 GHz), and the 3‐dB ARBW can cover 260 MHz (2.26‐2.52 GHz) and 2.48 GHz (3.9‐6.38 GHz). The designed antenna can be applied to the WLAN (2.4/5.2/5.8‐GHz) and WiMax (5.5 GHz) multi‐function and multi‐mode communication systems felicitously.